Studies on condensed 1,4-dihydropyridine derivatives and their calcium modulatory activities - (:unkn) unknown (GOVI-VERLAG PHARMAZEUTISCHER VERLAG GMBH, 2006)
Hexahydroquinoline and furoquinoline derivatives were synthesized and their calcium modulatory activity was investigated on isolated rat ileum and lamb carotid artery. In addition, the in vitro hepatic microsomal biotransformation of one hexahydroquinoline derivative was studied in rat microsomes.
Keywords: CHANNEL ANTAGONISTS; HEXAHYDROQUINOLINONES; PHARMACOLOGY; ACTIVATORS; BLOCKERS; CA-2